Zircon U–Pb geochronology and clockwise P–T evolution of garnet-bearing migmatites from the Qinling complex in the Weiziping area of the Qinling Orogen, Central China: Implications for thermal relaxation after crustal thickening. (15th June 2020) - Zhao, Yuhang; Gou, Longlong; Long, Xiaoping; Xu, Xiaofei; Zhou, Feng
Graphical abstract: Highlights: Garnet-bearing migmatites record a clockwise P–T path. The thermal relaxation after crustal thickening induced partial melting at ca. 409–395 Ma. The continental collision between the NQB and SQB should occur no later than ca. 409 Ma. Abstract: Zircon U–Pb dating and phase equilibrium modeling in the Na2 O–CaO–K2 O–FeO–MgO–Al2 O3 –SiO2 –H2 O–TiO2 –O2 system were carried out to garnet-bearing migmatites from the Qinling Complex in the Weiziping area of the Qinling Orogen, Central China, to constrain their metamorphic P–T path and elucidate the tectonic setting and geodynamic mechanism of Early to Middle Devonian high-temperature (HT) metamorphism in the North Qinling Belt. The mesosomes of the migmatites are composed of garnet-bearing biotite–hornblende–plagioclase and biotite–plagioclase gneisses, and the leucosomes can be divided into two types: wide leucosomes that were deformed, and narrow penetrative leucosomes. Laser ablation–inductively coupled plasma–mass spectrometry (LA–ICP–MS) zircon U–Pb analyses yielded weighted mean 206 Pb/ 238 U ages of 398.8 ± 4.7, 394.6 ± 2.6, 399.5 ± 7.3, 372.5 ± 4.2, 370.8 ± 4.3, and 368.5 ± 4.2 Ma for metamorphic zircons within the sampled mesosomes, and a weighted mean age of 408.7 ± 5.7 Ma for igneous zircons within a deformed leucosome. Based on the published data and the results in this study, the timing of granulite-facies metamorphism is constrained to be ca. 409–395 Ma. The mesosome sample (garnet-bearing biotite–hornblende–plagioclase gneiss) has a peak mineral assemblage of garnet, biotite, plagioclase, hornblende, quartz, ilmenite, and melt, which equilibrated at P–T condition of 8.5–9.7 kbar at 745–820 °C as constrained by isopleths of X An and X Py in a P – T pseudosection, suggesting that these gneisses underwent medium-pressure granulite-facies metamorphism. Conventional garnet–biotite–plagioclase–quartz (GBPQ) geothermobarometry yielded P–T conditions of 703 °C at 10 kbar and 685–748 °C at 7.1–8.9 kbar, which correspond to prograde and retrograde metamorphic stages, respectively. On the basis of these P–T results, the studied samples document a clockwise P–T path characterized by temperature increase and pressure decrease during the prograde stage, and temperature decrease and pressure decrease during the retrograde stage. Ti-in-zircon thermometry yielded a temperature range of 781–793 °C for metamorphic zircons from the mesosomes, further demonstrating that they underwent granulite-facies metamorphism at ca. 409–395 Ma. The prograde metamorphic stage characterized by temperature increase and pressure decrease suggests that thermal relaxation after crustal thickening has induced the partial melting and migmatization. Thus, the crustal thickening that may be caused by continental collision between the North China Block and the South China Block should occur no later than ca. 409 Ma.